Investigating The Financial Behavior In Batam’s Younger Generations: Does Financial Self-Efficacy Mediate? - Marheni, Dewi Khornida; Tazkia, Putri; Hashim, Hanini Ilyana Che; Wijaya, Cynthia Anna; Yuwono, Wisnu (Jurnal Dinamika Manajemen, 2025)
This study examines the financial behavior of Generation Y and Z in Batam by highlighting the role of psychological factors. Unlike previous research that emphasizes low financial literacy as the primary cause of poor financial behavior, this study explores how locus of control and financial self-efficacy mediate or moderate that relationship. Using a causal research design, snowball sampling technique, and online questionnaires, the findings reveal that both financial literacy and locus of control significantly influence financial behavior, with financial self-efficacyserving as a mediator. These results suggest that financial behavior is shaped not only by financial literacy but also by psychological factors such as self-control. The practical implication is the need for financial education programs that enhance not only knowledge but also psychological skills to support more informed financial decision-making.